A new approach for assessment of clubfoot treatment using non-radiological scanner coupling finite element - Liu, Shoushen; Zhang, Dongfang; Lv, Xiao; Huan, Xinjie; Li, Fujiang (Frontiers in Pediatrics, 2026)
IntroductionTo develop a new approach for clubfoot treatment assessment using a non-radiological scanner and finite element method (FEM) simulation techniques, which could eliminate the 8% risk of x-ray exposure, as well as evaluate the strain at the Achilles tendon.MethodsThe geometry of the clubfoot was acquired by using an optical-light-based scanner. The 3D model was generated from the geometry and exported to finite element simulation software. The contact and large deformation model was established to 13 simulate the angle correction of the Ponseti therapy. The strain and pseudo strain 14 rate were calculated from the simulation results and analysed for assessment.ResultsThe simulated stress distribution showed the stress concentration around the Achilles tendon, which coincides with the actual situation. The strain and pseudo strain rate were analysed with the correction angle, which matches the three-stage casting of Ponseti therapy. The result suggested the intermediate angle correction casting was 40% and 87% of the correction process. The recommended correction angles for coronal, axial, and sagittal axes were α = 17.2°, β = −2°, and γ = 13.2° for the first casting, and α = 35.6°, β = −4.4°, and γ = 25.4° for the second casting.ConclusionUsing the proposed approach has led to good correlation between the simulation results and the actual situation. It was feasible to use a non-radiological scanner coupled with FEM to evaluate the clubfoot treatment, which eliminates the risk of x-ray exposure for infants.